A novel LC-MS/MS method for mepivacaine determination and pharmacokinetic study in a single-dose two-period crossover in healthy subjects. (17th November 2017) - Duan, Ruo-Wang; Song, Jiong; Li, Yu-Ping; Xing, Chun-Gen
Abstract: The objective of this work was to develop a simple, selective, and sensitive LC–MS/MS method for the quantitation of the mepivacaine in Chinese biological matrix. The calibration curve of mepivacaine ranged from 0.5 to 2000 ng/mL with the lower limit of quantitation being 0.5 ng/mL. This sensitivity was high enough to describe the profile of blood mepivacaine level versus time. Thereby it was very desirable for the pharmacokinetic study because of its high sensitivity and accuracy. The study used a single-dose two-period crossover design principle. For the pharmacokinetic analysis of plasma, the mean (SD) values obtained were as follows: t1/2, 1.63 (0.43) h; C max, 435.3 (67.4) ng/ml; AUC 0-t, 1546.9 (339.7) ng/ml·h; AUC 0-∞, 1982.3 (421.4) ng/ml·h; T max, 0.62 (0.31) h. The validated method has been successfully applied to assess the pharmacokinetic study of mepivacaine after a single administration to Chinese volunteers.